Case reportCoexistence of Parry-Romberg syndrome with homolateral segmental vitiligo - Janowska, Marta; Podolec, Katarzyna; Lipko-Godlewska, Sylwia; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Parry-Romberg syndrome or progressive facial hemiatrophy was first described by Caleb Parry in 1825 and Moritz Romberg in 1846. This disorder is characterized by slowly progressing acquired unilateral hemifacial atrophy, which affects subcutaneous tissue together with the muscles and underlying bones. The pathogenesis and precise incidence of the syndrome remain unclear. Immune-mediated processes and disturbed central regulation, leading to the hyperactivity of the sympathetic nervous system, are primarily considered in the pathogenesis of this disorder. Parry-Romberg syndrome and localized scleroderma are considered to be interrelated as both of them have a similar clinicopathological appearance. We report the case of a 46-year-old man affected by both progressive atrophy of the left side of the face and homolateral, segmental vitiligo in the left side of the trunk and face.